Anteseden Job Performance Karyawan Perhotelan Bintang 3 dan Bintang 4 di Jakarta Barat - Fadel A'la An Nasher; Netania Emilisa; Diko Juandra (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study found that organizational resilience, anticipated positive affects, job satisfaction has a significant effect on job performance. Job satisfaction has also been shown to have a significant impact on job performance. Organizational resilience is also proven to have a significant effect on job satisfaction, and the anticipated positive affects also have a significant effect on job satisfaction. The purpose of this research is to identify the factors that affect the job performance of three-star and four-star hotel employees in West Jakarta. A quantitative methodology was used in this study and a random sample of 131 employees was selected. The hypothesis was tested using a structural equation model (SEM) using the AMOS statistical program version 26. Organizational results were studied in the field of human resource management and hospitality. Researchers in the field still see CSR as a promising and potential field. Drawing for singles Based on attention and attribution theory.